Platos Symposion und die Septuagintafassung von Genesis 2,23f. Methodische Ã?berlegungen zum Austausch von hebrÃ¤ischem und griechischem Sprach- und edankengutin der Klassik und im Hellenismus - Daphnē, Euangelia (Old Testament essays, 2006)
There is no doubt, that a meeting of minds and languages between the Ancient Greeks and the people of the Old Testament took place in the Classical as well as in the Hellenistic period. This fact finds expression especially in the Platonic works. But how did Plato come to consult and criticize very particular Old Testamental formulations and arguments in his works? And how did the Hebrew Scriptures and their Septuagint translators face his endeavour to understand and explain the Hebrew theological and anthropological thought? My purpose in writing this article is to give some methodological insights into this problem field using as concrete examples the Septuagint version of Gen 2,23f. and the speech of Phaidros in the Platonic Symposion (178a-180b). Special attention has also been paid to the tragedy Alcestis of Euripides.